Analysis of Modality in EFL Textbooks for Junior High School Students - Syafrayani, Putri Rizki (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
This study explores modality in English as a Foreign Language (EFL) textbooks, addressing a gap in prior research that emphasizes modal verbs’ frequency over their functional use. It analyzes the types and realization of modality in the Indonesian junior high school textbook English for Nusantara Grade VII using Halliday’s Systemic Functional Linguistics framework. Data, sourced from exercises, dialogues, and passages, were categorized into modalization (probability and usuality) and modulation (obligation and inclination). Findings indicate a prevalence of medium modality, with